Endoscopic sphincterotomy and cholecystectomy in acute biliary pancreatitis. Issue 2 (April 2016) - da Costa, D.W.; Schepers, N.J.; Römkens, T.E.H.; Boerma, D.; Bruno, M.J.; Bakker, O.J.; ,
Abstract: Background: This review discusses current insights with regard to biliary tract management during and after acute biliary pancreatitis. Methods: A MEDLINE and EMBASE search was done and studies were selected based on methodological quality and publication date. The recommendations of recent guidelines are incorporated in this review. In absence of consensus in the literature, expert opinion is expressed. Results: There is no role for early endoscopic retrograde cholangiopancreatography (ERCP) in patients with (predicted) mild biliary pancreatitis to improve outcome. In case of persisting choledocholithiasis, ERCP with stone extraction is scheduled electively when the acute event has subsided. Whether early ERCP with sphincterotomy is beneficial in patients with predicted severe pancreatitis remains subject to debate. Regardless of disease severity, in case of concomitant cholangitis urgent endoscopic sphincterotomy (ES) is recommended. As a definitive treatment to reduce the risk of recurrent biliary events in the long term, ES is inferior to cholecystectomy and should be reserved for patients considered unfit for surgery. After severe biliary pancreatitis, cholecystectomy should be postponed until all signs of inflammation have subsided. In patients with mild pancreatitis, cholecystectomy during the primary admission reduces the risk of recurrent biliary complications. Conclusion: Recent research has provided valuable data to guide biliary tract management in the setting of acute biliary pancreatitis with great value and benefit for patients and clinicians. Some important clinical dilemmas remain, but it is anticipated that on-going clinical trials will deliver some important insights and additional guidance soon.